SPECIFICS OF DEVELOPING A TEACHER’S CAPACITY FOR SELF-ANALYSIS AS A MANIFESTATION OF THE INDIVIDUAL-PERSONAL APPROACH (World Bulletin of Education and Learning, 2026)
This article reveals the individual-personal interaction between the teacher and students in the pedagogical process.
Keywords: Individual-personal, personality, interaction, teacher, student, process.